Submerged on the Surface : The Not-So-Hidden Jews of Nazi Berlin, 1941-1945 - Lutjens, Richard (Berghahn Books, 2018)
"Between 1941 and 1945, some 6,500 Berlin Jews, in fear for their lives, made the choice to flee their impending deportations and live submerged in the shadows of the capital of Nazi Germany. The experience was brutally difficult, and most did not survive. Yet the experiences of 1,700 who did demonstrate a remarkable and hitherto unconsidered level of agency among the survivors. This book sheds light on the daily life of those who hid and on the city that was both the source of their persecution and the site of their survival."